A model for personal financial planning towards retirement - Herrador-Alcaide, Teresa C.; Hernández-Solís, Montserrat; Topa, Gabriela (Journal of Business Economics and Management, 2021)
One problem for sustainability of systems pensions is how people without specialized financial training could manage their resources and their actual personal intentions towards retirement.Research objective is to analyse the relationship among several factors that affect the behaviour towards retirement, the financial management practices and the financial resources, by carrying out a structural equation model (SEM) that was tested in Spanish workers sample in three phases.  The influence of financial literacy, financial retirement objectives, optimism on retirement, tolerance to financial risk, and the commitment to financial planning at time 1, are analysed as explanatory variables of financial management practices at time 2. Financial resources for retirement at time 3 are explained by financial management practices.According to results, the model can predict the 36% of the variance of financial management practices and 53% of the variance of financial resources for retirement. Thus, the model can be used for checking of knowledge of the personal financial behaviour before retirement, what enables a better personal financial planning. It would be possible to apply a model based on self-assessment in order to implement a complementary financial planning that would allow to maintain the welfare during retirement.First published online 30 December 2020